Pemanfaatan Video YouTube tentang Anemia pada Remaja Putri di SMK YPSEI Palangka Raya - Erina Eka Hatini; Noordiati Noordiati (Jurnal Surya Medika (JSM), 2021)
Prevalence of anemia is about 29% (496 million) in women who are not pregnant, and about 38 % or 32.4 million pregnant women aged 15-49 years are anemic. (WHO, 2014 ) . About 23% of adolescent girls experience anemia due to iron deficiency and have low knowledge about anemia. This study aims to analyze the use of Video Youtube to increase the knowledge of young girls about Anemia. This study was using one design group comparison pretest-posttest design. About 96% of respondents are 14-16 years old, 4% of respondents are ≥17 years old. As many as 100% of young girls know information about anemia from health education by health workers. Around 64 % of young girls experience menstruation around the age of 10-13 years, 36 % at age 14-16 years. Analysis using the Wilcoxon test, the average score of girls knowledge was 52.00 before the intervention and after the intervention, the average knowledge score of the young girls was around 83.60. The analysis has obtained a p-value of 0.000 (p <0.05), which indicates the intervention counseling video increases young girls' knowledge about anemia significantly.